The response of euro area sovereign spreads to the ECB unconventional monetary policies - Hans Dewachter; Leonardo Iania; Jean-Charles Wijnandts (National Bank of Belgium, 2016)
We analyse variations in sovereign bond yields and spreads follow- ing unconventional monetary policy announcements by the European Central Bank. Using a two-country, arbitrage-free, shadow-rate dynamic term structure model (SR-DTSM), we decompose countries' yields into expectation and risk premium components. By means of an event study analysis, we show that the ECB's announcements re- duced both the average expected instantaneous spread and risk repricing components of Italian and Spanish spreads. For countries such as Belgium and France, the ECB announcements impacted primarily the risk repricing component of the spread.
Keywords: 330; Geldpolitik; Wirkungsanalyse; Öffentliche Anleihe; Rendite; Eurozone